KAJIAN KAPASITAS LENTUR BALOK BETON BERTULANGAN BAMBU PETUNG DENGAN TAKIKAN TIDAK SEJAJAR - Perwira, Eka; Budi, Agus Setiya; Utomo, Budi (Matriks Teknik Sipil, 2013)
Bambu is an alternative substitution for steel reinforcement with sufficiently high impressive strength. The bambu- reinforcement model approach was conducted by making notch on the reinforcement edge. It aimed to improve the adhesiveness of bambu and concrete just like that used in steel deformed bar. This study aimed to find out the elasticity strength of petung bambu-boned concrete beam with nonaligned notch in normal concrete. The research method used was a laboratory experiment carried out in Material and Structure Laboratory of Engineering Faculty of Surakarta Sebelas Maret University. The tested material was concrete beam 1500 mm in length, 100 mm in width, and 150 mm in height. The testing was conducted using four-point loading. The smooth steel reinforcement used was 10 mm in diameter. The bambu used was the reinforcement was petung bambu aged above 2,5 years in air dry condition and water level less than 30% deriving from Jatipuro area of Karanganyar. The notching treatment on the reinforcement was the nonaligned one on bone edge with the notch's dimension of 15 mm, depth of 5,2 mm and notches space of 100 mm. The result of examination on the concrete beam tested object with 10 mm-diameter smooth steel reinforcement obtained the elasticity value of 484,8924 kg-m and the value analysis calculation of 386,912 kg-m. The result of examination on the concrete beam tested object with petung bambu reinforcement with nonaligned notch obtained the elasticity value of 218,395 kg-m and the value analysis calculation of 161,8194 kg-m.